Comparisons between the Wake of a Wind Turbine Generator Operated at Optimal Tip Speed Ratio and the Wake of a Stationary Disk. (3rd April 2011) - Uchida, Takanori; Ohya, Yuji; Sugitani, Kenichiro
Abstract : The wake of a wind turbine generator (WTG) operated at the optimal tip speed ratio is compared to the wake of a WTG with its rotor replaced by a stationary disk. Numerical simulations are conducted with a large eddy simulation (LES) model using a nonuniform staggered Cartesian grid. The results from the numerical simulations are compared to those from wind-tunnel experiments. The characteristics of the wake of the stationary disk are significantly different from those of the WTG. The velocity deficit at a downstream distance of10 D (D : rotor diameter) behind the WTG is approximately 30 to 40% of the inflow velocity. In contrast, flow separation is observed immediately behind the stationary disk (≤ 2 D ), and the velocity deficit in the far wake (10 D ) of the stationary disk is smaller than that of the WTG.